Quantification and characterization of ultravioleta-B radiation in the city of Tacna, period: 2012-2014: Collaboration with the XXIII Peruvian Symposium on Solar Energy - Polo Bravo, Carlos (2020)
The objective is to quantify and characterize the ultraviolet B radiation on the city of Tacna using the basic ultraviolet B (UV-B) radiation information corresponding to the period 2012 - 2014, registered in the main agricultural meteorological station MAP-Jorge Basadre Grohmann, city of Tacna, operated by SENAMHI, through the measurement of the ultraviolet radiation index (IUV). The ultraviolet B radiation indices determined at the daily, monthly, seasonal and multi-annual levels reached maximum values ​​of 8 to 10 at very high risk levels and 11 at extremely high risk levels in the months of January, February, November and December with frequencies of occurrence 67% and 33%, while the minimum rates recorded were 3 to 5 with a moderate level of risk in the hours of 8:00 am and 5:00 pm, with frequencies of 40% and 83% during the months of June and July respectively. The results obtained constitute important indicators to take preventive measures for the population against exposure to UV-B ultraviolet radiation and minimize its harmful effects on health.